CESAREAN SECTION IN UKRAINE AND THE UNITED KINGDOM: SIMILARITIES AND DIFFERENCES - Л. Лазуренко; О. Железняков; С. Алхімов; О. Овчаренко; Р. Сафонов; Д. Тертишник (Неонатологія, хірургія та перинатальна медицина)
The aim of the study was to conduct a comparative analysis of cesarean sections in Ukraine and the United Kingdom in order to improve the quality of medical care and optimize outcomes for both mother and newborn. Materials and methods. To achieve this goal, we analyzed the unifi ed clinical protocol «Caesarean section» of the Ministry of Health of Ukraine dated January 5, 2022 and the UK NICE GUIDELINE «Caesarean birth» in the latest version dated September 6, 2023. The work was performed in accordance with the research plan of the Department of Obstetrics and Gynecology #2 of KhNMU: «Optimization of diagnostics, treatment of diseases of the reproductive system and pregnancy complications in women with extragenital pathology» (state registration number 0121U11923). Results. A comparative study of cesarean section protocols in Ukraine and the United Kingdom provided important insights into the current state of obstetric practice in both countries. Signifi cant diversity in CS protocols in Ukraine and the UK was noted. This is particularly true for both clinical aspects and aspects related to organizational and sociocultural factors. A signifi cant infl uence of social and cultural factors in the UK on the frequency of CR was found. The diff erence between the Ukrainian medical system and the NHS in the UK is mainly in the control of narcotic analgesics, the duration of the postoperative period, and the consideration of the woman’s preference for the method of delivery is quite controversial. Conclusions. Negative statistics reveal that the increase in the frequency of CS is typical not only for the UK, but also for Ukraine, although in Ukraine the explanation for this situation is the increase in the frequency of obstetric and extragenital pathology during martial law, and in the UK it is the woman’s choice. Understanding the diff erences between countries in their approaches to CS will help improve the quality of medical care and optimize outcomes for both mother and newborn. Understanding the differences between countries in their approaches to CS will help to improve the quality of medical care and optimize outcomes for both mother and newborn.